Being right vs. getting it right: orientation to being recorded in psychotherapeutic interaction as disaffiliative vs. affiliative practice - Franzen, Michael M.; Alder, Marie-Luise; Dreyer, Florian; Köpp, Werner; Buchholz, Michael B. (Frontiers in Psychology, 2023)
Introduction The study focuses on the orientation to being recorded in therapy sessions, emphasizing that these practices adapt to specific circumstances and influence subsequent actions. The study suggests a way to deal with the insolubility of the “observer paradox”: to accept that observation has an impact on the observed, but that the recorder is not necessarily a negative determinant. Furthermore, the study builds on the idea that participants' orientations to the recorder can be seen as actions. Methods The data included in this study were collected from four psychodynamic therapies. A total of 472 sessions were searched for orientation to be recorded. Twenty-three passages were found and transcribed according to GAT2. Of the 23 transcripts, six excerpts have been analyzed as part of this article. The analysis of this study was done through Conversation Analysis. Results The study explores how participants use the orientation to be recorded to initiate or alter actions within conversations, which can help achieve therapeutic goals, but can also hinder the emergence of a shared attentional space as the potential to disrupt the therapist-patient relationship. The study identifies both affiliative and disaffiliative practices, noting that managing orientation to be recorded in a retrospective design consistently leads to disruptive effects. Moreover, it highlights the difference between seeking epistemic authority (“being right”) and managing recording situations (“getting it right”) in therapeutic interactions as a means of initiating patients' self-exploration. Discussion The integration of recordings into therapeutic studies faces challenges, but it's important to acknowledge positive and negative effects. Participants' awareness of recording technologies prompts the need for a theory of observation in therapeutic interactions that allows therapists to visualize intuitive practices, incorporate active contributions, counteract interpretive filtering effects, facilitate expert exchange, ensure quality assurance, and enhance the comprehensibility of therapeutic processes. These aspects outline significant variables that provide a starting point for therapists using recordings in therapeutic interactions.